Are there predictors that can determine neoadjuvant treatment responses in rectal cancer? - Sema Yılmaz Rakıcı; Recep Bedir; Celile Hatipoğlu (Turkish Journal of Gastroenterology, 2019)
Background/Aims: This study aimed to determine a predictive bioindicator that would detect the treatment response of patients diagnosed with rectal cancer and treated with neoadjuvant chemoradiotherapy (nCRT). Materials and Methods: The data collected from 37 patients receiving nCRT were retrospectively evaluated. The p53 score and gene instability in MLH1 and MSH2, which are among the DNA mismatch repair (MMR) genes, were evaluated using immunohistochemical methods. The neutrophils-leukocytes ratio (NLR), carcinoembryonic antigen (CEA), and carbohydrate antigen (CA) 19-9 values were obtained as hematological parameters from computer records. The pathologic analysis of the therapy response after nCRT was classified according to the modified grading system by Ryan et al. Results: The changes in the NLR, CEA, and CA19-9 values before and after treatment were statistically significant (p≤0.001 and p=0.005). A near significant effect of the decrease of the CEA value in the 5th week after treatment was detected on the pathological response score (p=0.075). The p53 mutation score in those patients with any residue was higher than the total response. Overall, 89.2% of the patients exhibited MMR positivity (stability), and 10.8% of the cases with MRM negativity (instability) had a macroscopic residue. Cases with pathological total response were MRM positive. Conclusion: Consequently, in most of the patients treated with nCRT, the treatment caused tumor and nodal remission. In the prediction of this therapy response, hematological and genetic parameters, such as NLR, P53, MLH1, and MSH2, play a predictive role. Cite this article as: Yılmaz Rakıcı S, Bedir R, Hatipoğlu C. Are there predictors that can determine neoadjuvant treatment responses in rectal cancer? Turk J Gastroenterol 2019; 30(3): 220-7.